Multivalued adaptive neuro-fuzzy controller for robot vehicle - art. no. 1406 - Garbi, Giuliani Paulineli [UNESP]; Gamarra Rosado, Victor Orlando [UNESP]; Grandinetti, Francisco Jose [UNESP] (Atlantis Press, 2007)
Robotic vehicle navigation in unstructured and uncertain environments is still a challenge. This paper presents the implementation of a multivalued neurofuzzy controller for autonomous ground vehicle (AGVs) in indoor environments. The control system consists of a hierarchy of mobile robot using multivalued adaptive neuro-fuzzy inference system behaviors.
Keywords: multivalued; adaptive neuro-fuzzy; mobile robot